2018
DOI: 10.1038/s41431-018-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of dementia in a Finnish cohort

Abstract: Alzheimer's disease (AD) and frontotemporal dementia (FTD) are the two most common neurodegenerative dementias. Variants in APP, PSEN1 and PSEN2 are typically linked to early-onset AD, and several genetic risk loci are associated with late-onset AD. Inherited FTD can be caused by hexanucleotide expansions in C9orf72, or variants in GRN, MAPT or CHMP2B. Several other genes have also been linked to FTD or FTD with motor neuron disease. Here we describe a cohort of 60 Finnish families with possible inherited deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Some CNVs affected genes that are specifically expressed in the brain, and/or constrained against deletions and loss of function mutations, (Figure and Supplementary Information Appendix S1: list “constrains and expression”), identifying them as novel candidate genes for impulsive behavior. These genes included FBXL16 , PHACTR3, CDH20, FAM155A , DOK6, NKAIN2 , STXBP5L , or PCDH9 , UNC13C , and DPP10, C7orf26 , FSD1 , GLT8D1 , or GNL3. Other candidate genes included DNAJC15 and UBE2V2.…”
Section: Resultsmentioning
confidence: 99%
“…Some CNVs affected genes that are specifically expressed in the brain, and/or constrained against deletions and loss of function mutations, (Figure and Supplementary Information Appendix S1: list “constrains and expression”), identifying them as novel candidate genes for impulsive behavior. These genes included FBXL16 , PHACTR3, CDH20, FAM155A , DOK6, NKAIN2 , STXBP5L , or PCDH9 , UNC13C , and DPP10, C7orf26 , FSD1 , GLT8D1 , or GNL3. Other candidate genes included DNAJC15 and UBE2V2.…”
Section: Resultsmentioning
confidence: 99%
“…ECSIT (down‐regulated with age) was the top‐ranked hub gene in the age transcriptome (Figure and Appendix ). Composed of 209 genes, the ECSIT network included CADM2, UNC13C and ST3GAL3 genes, with variants linked to cognition (Pasanen et al, ). ECSIT promotes NFκB activity (Wi et al, ), and in AD experimental models, repression of NFκB activity decreases BACE1 activity and both soluble and insoluble Aβ (Paris et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported as one of the hub genes in a genome-wide association study of post-traumatic stress disorder in Iraq-Afghanistan veterans [27]. Unc13c has also been found to be associated with neurodegeneration in a genetic dementia in Finland [28]. These studies suggested that Unc13c could be closely associated with the CNS, and it could be a target gene for reducing PND.…”
Section: Discussionmentioning
confidence: 99%